Signal transduction of vitamin K3 for pancreas cancer therapy - Toshiyuki Tanahashi; Shinji Osada; Hisashi Imai; Yoshiyuki Sasaki; Takao Takahashi; Kazuya Yamaguchi; Kazuhiro Yoshida (Frontiers Media S.A., 2011)
We characterized molecular mechanisms of vitamin K3 (VK3)-induced inhibition of proliferation to evaluate VK3 effectiveness in treating advanced pancreatic cancer. A novel endoscopic drug delivery system, ultrasound injection technique, was used to study local effects of VK3. VK3 inhibited pancreas cancer cell growth by rapid phosphorylation of growth factor receptor and cellular signal factors such as extracellular signal-regulated kinase. VK3 also activated apoptosis, and apoptosis inhibitor antagonized the apoptosis pathway without inhibiting cell growth. Thiol antioxidant treatment completely abrogated VK3-induced ERK but not JNK phosphorylation or inhibition of proliferation. Non-thiol antioxidant did not affect ERK phosphorylation or growth inhibitory actions. Arylation was considered the main mechanism of VK3-induced growth inhibition through ERK activation. VK3 may lead to favorable outcomes in the treatment of pancreatic tumors. Detection of ERK phosphorylation in tissue is important to predict VK3 effect. Endoscopic ultrasound-guided fine-needle injection may be beneficial for treating pancreatic cancer with VK3.